Moodle como ferramenta de gestão educacional aplicada aos professores de educação física - Kraemer, Débora Riograndense (2015)
This work approaches a research on insertion and applicability of Moodle as an Educational Management tool, which was prospected to build a mean of communication with interaction and interactivity between Physical Education teachers from Secretaria Municipal de Educação de São Sepé RS and the responsible sports manager from this department. First of all, literature revision took place about understanding and concepts from some authors in a sense to clarify and understand the research problem: which pretends to identify the limits and possibilities of insertion and applicability of Moodle as an Educational Management tool in Physical Education allowing interaction and interactivity? Next, the analysis, insertion and application of this Educational Management tool, enabling communication between Physical Education teachers which belong to the teachers from Secretaria Municipal de São Sepé RS staff. An in-person training with physical education teachers of São Sepe Municipio which had its first guidelines on the use of Virtual Environment Moodle and its available resources to carry out the proposed activities took place. After the virtual daily monitoring for encouragement and clarification of doubts. The funds were used as polls, forums, wiki where they could exchange ideas, interact and create the end of the work, a collaborative text with the following topic: Physical education and its relationship with technology in school. This work is divided in three chapters that cover from contextualization, conceptualization and analysis of the applicability and insertion of Moodle in this environment. Following the Theoretical and Methodological Guides that are presented from authors as: Castells(2003/2013), Taspscott & Williams(2007), Moran(2013), Mendes (2008) e Betti (2006) among others that make us realize the need to integrate our educational activities using Moodle as an Educational Management tool. Beyond going deeper on studies about the importance of these educational resources, can be observed that this Virtual Learning Environments present an incredible variety of pedagogical and communicational practices and postures, providing exchange of experiences about the reality in the school routine context. As possibilities and limits of using Moodle as na Educational Management tool are important to promote in a more dynamic way the communication between the Physical Education teachers from Secretaria Municipal de Educação and exchange of experiences, questions and suggestions from all participants. It is aimed to the possibility of widespread the use of Moodle as an Educational Management tool and communication while trying to reach all teachers from diverse educational areas in the municipal basic school system. At last, the final product of this research was the collaborative construction, between all participants, of a Wiki that resulted in the creation of a text about: What is the role of the Physical Education teacher against the Technologies adopted in Schools , making them question and think about their actions against these technologies adopted in the educational sector.